2013
DOI: 10.1038/jid.2012.333
|View full text |Cite
|
Sign up to set email alerts
|

mTORC2-PKBα/Akt1 Serine 473 Phosphorylation Axis Is Essential for Regulation of FOXP3 Stability by Chemokine CCL3 in Psoriasis

Abstract: The connection between infections and acute guttate psoriasis (AGP) outbreaks/chronic plaque psoriasis (CPP) exacerbation has been known for years. Impaired function of FOXP3+Tregs in psoriasis has been identified. However, the mechanisms behind these two observations have not been fully interpreted. In the present study, we provide evidence to support chemokine CCL3 as one of the vital links between infections and FOXP3 stability in the psoriatic microenvironment. We found that serum CCL3, strongly induced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 49 publications
1
24
0
Order By: Relevance
“…The CCL3 , IL19 and IL20 genes have been described to be upregulated in untreated lesional psoriatic skin, [4042] and they were downregulated 4 days after adalimumab treatment start. Finally, IL1α and IL1β were downregulated after 4 days of adalimumab treatment start.…”
Section: Discussionmentioning
confidence: 99%
“…The CCL3 , IL19 and IL20 genes have been described to be upregulated in untreated lesional psoriatic skin, [4042] and they were downregulated 4 days after adalimumab treatment start. Finally, IL1α and IL1β were downregulated after 4 days of adalimumab treatment start.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CC-chemokine ligand 3 (CCL3), which is abundant in patients with psoriasis, has been reported to induce T reg cell dysfunction and plasticity by triggering the K48-linked polyubiquitylation and degradation of FOXP3 (REF. 105). …”
Section: Post-translational Modification Of Foxp3mentioning
confidence: 99%
“…The extreme inflammatory microenvironment seen during psoriasis is a setting in which Foxp3 + Tregs exhibit ineffectiveness and plasticity (213). A link between infections and psoriasis outbreaks has been proposed, and recently, Chen et al (214) explored a potential connection hinging on Treg instability. Specifically these authors found a negative correlation between Foxp3 protein levels in the CD4 + CD25 + cells of psoriasis patients and serum levels of CCL3, a chemokine and hallmark of streptococcol infection.…”
Section: Chemokinesmentioning
confidence: 99%